Tuberculosis screening among cough suppressant buyers in pharmacies and drug outlets in Guinea: a cross-sectional study - Jonathon R Campbell; Vanessa Veronese; Aboubacar Sidiki Magassouba; Almamy Amara Toure; Boubacar Djelo Diallo; Gnoume Camara; Desire Lucien Dahourou; Aly Badara Nabe; Souleymane Camara; Adama Marie Bangoura; Hugues Asken Traore; Corinne Simone Collette Merle (BMJ Open Respiratory Research)
Background Tuberculosis (TB) poses a significant public health challenge in Guinea, with an estimated 22 000 TB cases in 2020; an estimated 6125 (28%) cases went undetected. We evaluated an intensified TB case finding strategy in Guinea which targeted customers who bought cough suppressants from pharmacies or drug outlets.Methods We involved 25 pharmacies and 25 drug outlets in Matoto, Conakry, Guinea. Pharmacists or outlet owners identified and referred all customers with TB symptoms who were purchasing cough suppressants to healthcare workers for sputum collection either at the pharmacy or drug outlet or at a nearby TB diagnosis and treatment centre (CDT); sputum was subjected to bacteriological testing with acid fast bacilli smear or Xpert MTB/RIF. We assessed factors associated with eventual TB diagnosis using logistic regression and time to TB diagnosis using cox regression and used microcosting to estimate the cost of the intervention in 2020 US$.Results From November 2019 to June 2020, we screened 916 people referred from pharmacies or drug outlets with TB symptoms, with median age of 31 years (54% male). Overall, 126 (14%) had bacteriologically confirmed TB. Odds of TB diagnosis were significantly lower with increasing age (adjusted OR (aOR) per additional year=0.98; 95% CI 0.97 to 0.99) and higher among males (aOR=1.57; 95% CI 1.04 to 2.39) and those with symptoms. Those identified at drug outlets had significantly faster time to presentation from symptom onset than pharmacies (adjusted HR=1.73; 95% CI 1.50 to 1.99). The total cost of the intervention per person referred was US$32.66 and per person diagnosed and treated for TB disease of US$237.45.Conclusion Intensified TB case finding through pharmacies and drug outlets is a feasible and effective way to increase TB detection in settings where self-medicating is common, and TB is under-detected.